Effects of gallic acid on the morphology and growth of hydroxyapatite crystals. Issue 1 (January 2015) - Tang, Bei; Yuan, He; Cheng, Lei; Zhou, Xuedong; Huang, Xuelian; Li, Jiyao
Highlights We carried out the experiment under relatively mild conditions. The aqueous ammonia diffusion co-precipitation method was used. Crystal from group with gallic acid showed urchin-like morphology. Gallic acid may limit the growth of the crystal, and this action mainly happened on 0 0 2 direction. The auto-fluorescence was detected, which proved the gallic acid participating into the precipitate.